Analisis Pertumbuhan Ekonomi di Negara BRICS - Fauzan, Ihda Budi; Anindyntha, Firdha Aksari (Jurnal Riset Ilmu Ekonomi, 2024)
Economic growth is one of the important economic indicators in the economy. The study aims to analyze the factors that influence economic growth in BRICS countries during the period 2008-2023. Independent variables are expected to affect economic growth in this study including primary sector commodities, trade, industry, and population. The method in this research uses fixed effect panel data regression model. The results explain that the factors that positively affect economic growth in BRICS countries are trade and industry. Meanwhile, the contribution of primary sector commodities and population have not significantly affected economic growth in BRICS countries. This research is expected to contribute to various aspects that have an impact on the global and regional economy, especially on BRICS countries (Brazil, Russia, India, China, and South Africa) in policy making that focuses on planning strategies to increase economic growth based on challenges and opportunities in global and international markets.